Pious Neoliberalism and the Rise of Middle-Class Muslim Education in West Sumatra - Ika Sandra; Rama Arya Kurniawan; Muhammad Alfian; Muhammad Rizki Alvarizi; Gigieh Cahya Permady (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
The rapid growth of modern Islamic boarding schools in Indonesia reflects a significant transformation in the relationship between religion, education, and contemporary social aspirations. While previous studies have predominantly examined Islamic education through the perspectives of institutional transformation, educational marketization, and parental school choice, limited attention has been given to understanding how Muslim middle-class families negotiate religious aspirations alongside neoliberal educational values. This study aims to examine the rise of Islamic boarding schools in West Sumatra through the perspective of pious neoliberalism, focusing on how families construct Islamic education as a strategy for producing pious, disciplined, and socially competitive children. This study employs a qualitative case study approach conducted in two modern Islamic boarding schools in West Sumatra, namely Ar-Risalah and Nurul Ikhlas. Data were collected through semi-structured interviews with parents, school leaders, and teachers, as well as direct observations of institutional practices. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal three interrelated dimensions of the emergence of pious neoliberal educational aspirations among Muslim middle-class families. First, Islamic boarding schools are perceived as controlled moral environments that protect children from contemporary social risks and cultivate religious discipline. Second, Islamic education has shifted into a form of long-term educational investment through which families seek to accumulate religious, cultural, and academic capital for future social mobility. Third, modern Islamic boarding schools contribute to the formation of an ideal Muslim subject who combines Islamic morality with academic achievement, global competencies, and competitiveness. This study argues that neoliberalism does not necessarily diminish the role of religion within education; rather, it reshapes religious aspirations by integrating piety with values of self-improvement, educational investment, and social distinction. The findings contribute to broader discussions on the neoliberal transformation of education, Muslim middle-class formation, and the changing nature of Islamic educational aspirations in contemporary societies.